2021
DOI: 10.3389/fpsyt.2021.767804
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Among Physical Literacy, Mental Health, and Resilience in College Students

Abstract: Objectives: The objective of the study is to examine the relationship among physical literacy, mental health, and resilience in college students.Methods: The study is a cross-sectional study. Participants (N = 5,265; 46.6% males) completed perceived physical literacy instruments, mental health continuum short forms, and the 12-item child and youth resilience measures. Mediation models were applied to explore the association among three concepts.Results: Physical literacy, resilience, and mental health were sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
20
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 52 publications
(77 reference statements)
3
20
0
2
Order By: Relevance
“…To the best of our knowledge, there is a lack of research on the mediating effect of resilience between stigma and mental disorders of COVID-19 survivors. A study conducted among college students indicated the partial mediating effect of resilience in the relationship between physical literacy and mental health [ 74 ]. The moderating role of resilience in the personality-mental health relationship during the COVID-19 pandemic also had been demonstrated [ 75 ].…”
Section: Discussionmentioning
confidence: 99%
“…To the best of our knowledge, there is a lack of research on the mediating effect of resilience between stigma and mental disorders of COVID-19 survivors. A study conducted among college students indicated the partial mediating effect of resilience in the relationship between physical literacy and mental health [ 74 ]. The moderating role of resilience in the personality-mental health relationship during the COVID-19 pandemic also had been demonstrated [ 75 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, higher levels of psychological resilience, and lower levels of anxiety symptoms of children and adolescents [24]. The same effect of resilience was found in the college student population [25]. In terms of social anxiety, some researchers have found that individuals with social anxiety disorders have lower levels of resilience compared with healthy controls [26].…”
Section: The Potential Mediating Role Of Psychological Resiliencementioning
confidence: 75%
“…The construct of physical literacy has been used in research with individuals who have various health and clinical conditions, including intellectual disabilities (Dudley et al, 2016), mental health disorders (Fortnum et al, 2018;Ma et al, 2021) and various medical conditions (Bopp et al, 2019;Do et al, 2021).Whilst the importance of physical literacy is growing in evidence within health, education and sport, there has been relatively little focus of how health professionals engage with the concept and might consider its use in clinical practice for therapy assessment and intervention. Healthcare professionals, including those that work in the allied health sector (e.g.…”
Section: Introductionmentioning
confidence: 99%